Dermatobia hominis: potencial risk of resistance to macrocyclic lactones - Neves, José Henrique das [UNESP]; Carvalho, Nadino [UNESP]; Amarante, Alessandro F. T. [UNESP] (Elsevier B. V., 2015)
Dermatobia hominis is an ectoparasite that infests various species of mammals, including cattle, impairing the quality of cowhides and leather. After observing natural infestation with D. hominis larvae in cattle on two farms in the state of São Paulo, Brazil, we evaluated the efficacy of two macrocyclic lactones, ivermectin and moxidectin, against this parasite. The drugs were administered to 10 animals in each group, following the manufacturer's instructions. The groups were: Group 1-treated with ivermectin (0.2mg/kg of body weight (BW)); Group 2-treated with moxidectin (0.2mg/kg BW); and Group 3-control (untreated). On the farm in Pardinho, a total of 12 and 16 live larvae were found in 6 and in 8 animals 10 days after the treatment with ivermectin and moxidectin, respectively, while in the control group 4 bovines had a total of 7 live larvae. On the farm in Anhembi, 2, 4 and 6 live larvae were extracted from ivermectin, moxidectin and control groups, respectively, after the treatment. This is the first report of the presence of live D. hominis larvae after the treatment of cattle with ivermectin and moxidectin in Brazil.
Keywords: Drug resistance; Ivermectin; Macrocyclic lactones